The Role of Banking Penetration in Achieving Competitive Advantage in Private Commercial Banks (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to demonstrate the impact of banking penetration and financial inclusion of the banks that will be studied on the competitive advantage for decent work and economic growth, as indicators were adopted to measure banking penetration by (banking penetration, banking density), and indicators to measure financial inclusion were represented by (ratio of the volume of deposits, overdue debts). Payment), and indicators to measure competitive advantage represented by (cost (expenses), quality (revenues)). The research problem was defined by the main question, which is (What is the impact of banking penetration and financial inclusion on competitive advantage?),The research was applied to private Iraqi commercial banks and a deliberate sample was chosen, represented by (Al-Khaleej Commercial Bank). The financial statements of the research sample bank for the years (2017-2022) were approved, and financial data analysis was used for the research hypotheses. The research reached conclusions, the most important of which are:• Banking penetration and financial inclusion are still below the level required for the banks in the research sample compared to the development taking place in providing banking services in terms of the development of modern technologies in providing banking services.• Poor banking penetration, comparing the number of branches divided by the population.• The financial inclusion of banks does not equal the increase in population.• There is a relationship between banking penetration and financial inclusion on competitive advantage.